Contraindications in national guidelines for vaginal breech delivery at term: Comparison, consensus, and controversy - Merle R. vanDijk; Christiaan Papatsonis; Wessel Ganzevoort; Etelka Moll; Fedde Scheele; Joost Velzel (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The optimal mode of delivery for vaginal breech presentation remains a clinical dilemma. Planned vaginal delivery offers maternal advantages because it avoids major abdominal surgery and has no consequences for following pregnancies, while elective cesarean delivery proves advantageous for the neonate because adverse outcomes are less frequent. Patient selection for vaginal breech delivery is important based on the individual risk balance. A lack of consensus exists regarding the specific contraindications for vaginal breech delivery, largely due to limited scientific evidence. This systematic review aims to give an overview of contraindications for vaginal breech delivery, as presented in guidelines, analyze relevant literature, and offer evidence‐based recommendations for the contraindications stated in the guidelines. Material and Methods To identify national guidelines PubMed, the Cochrane Central Register of Controlled Trials, EMBASE, NICE, UpToDate, and ClinicalKey were searched using two keywords: “breech presentation” and “vaginal delivery.” We systematically reviewed the literature for existing evidence for contraindications for term vaginal breech delivery. The following databases were searched: PubMed (April 2024), the Cochrane Central Register of Controlled Trials, and EMBASE (1947 to 2024). Results Our search identified eight guidelines that stated a total of 11 contraindications for vaginal breech delivery. Among these guidelines, agreement was limited, with the sole consensus in all guidelines on the contraindication of footling breech. Our comprehensive literature search yielded 43 articles discussing 14 potential contraindications. We found supportive evidence for 7 of 11 contraindications from the guidelines, with only substantial and satisfactory evidence for two contraindications. Conclusions The findings of this study underscore the lack of consensus among national guidelines regarding contraindications for term vaginal breech delivery. Furthermore, we found a notable lack of substantial scientific evidence to support these contraindications. In light of these findings, we suggest a reduced list of contraindications in vaginal breech deliveries.